Afghanistan and China : A Perspective on Geopolitical Relations and Strategic Interests - Hussain Ali Anosh (International Journal of Social Science and Humanity, 2025)
The geopolitical relations between China and Afghanistan have undergone significant transformations in recent years, shaped by regional dynamics, security imperatives, economic cooperation, and strategic interests. As a neighboring country with extensive global influence, China has adopted a pragmatic approach toward Afghanistan, seeking to balance its economic investments with security considerations. This study explores the historical trajectory of Sino-Afghan relations, identifies the key factors influencing their bilateral interactions, and examines Afghanistan’s strategic importance within the broader regional ambitions of China—particularly in relation to the Belt and Road Initiative (BRI). It also briefly investigates China's role in Afghanistan’s political landscape following 2001 and analyzes its evolving stance after the Taliban's return to power in 2021. Furthermore, the research highlights the economic, security, and diplomatic dimensions of the two countries’ relationship and evaluates how Beijing’s strategic calculations in Afghanistan align with its broader regional objectives—especially concerning security stability (counterterrorism) and economic expansion. From a geopolitical standpoint, this paper offers insights into the long-term implications of China’s engagement with Afghanistan and its broader impact on the regional power dynamics, using a descriptive-analytical methodology.